Profile of VO2 Max Level on South Sulawesi PPLM Athletes - Jalil, Rasyidah; Ahmad; Dahlan , Firmansyah (International Journal of Psychosocial Rehabilitation, 2020)
This research was descriptive (independent-variable). Population and samples were PPLM athletes of South Sulawesi selected in Non-Random Sampling with the technique of saturated samples obtained as many as 15 male and female athletes. Data analysis techniques used descriptive percentage. Based on data analysis results, it can be deduced the condition of the South Sulawesi PPLM athlete rate varies based on the classification for males: very good = 0%, good 2 people = 33.3%, sufficient 4 people = 66.7%, less = 0%, very less = 0% and obtained the score of mean = 49.0333 with standard deviation = 4.10593, variance = 16,859, range = 10.60, minimum = 42.40, and maximum = 53.00. Classification for women: very good = 0%, good 1 person = 11.1%, sufficient 5 people = 55.6%, less 3 people = 33.3%, very less = 0% and obtained with the score mean = 39.2611 with standard deviation = 4.48684, Variance = 20,132, range = 12.95, minimum = 33.25, and maximum = 46.20. Thus the overall extent can be concluded that the VO2Max level of PPLM athletes of South Sulawesi was dominant in sufficient category.